BREEDING ZONES BASED ON GENOTYPE-ENVIRONMENT INTERACTION IN SEEDLING SEED ORCHARDS OF Eucalyptus pellita IN INDONESIA - Budi Leksono (Indonesian Journal of Forestry Research, 2009)
The magnitude  of the genotype-environment interaction (GEI) in seven six years  old seedling  seed orchards  of Eucalyptus pellita established  at three locations  in Indonesia  was examined  by analyzing height  and diameter.  The seed orchard  at each location  consists of 121 families  from three  provenances  of Papua  New  Guinea.  The pooled  sum of squares derived from analysis  of variance  of growth  of the three provenances  was used to estimate genetic  parameters.  These parameters  were  then used to calculate  genetic  gain as a result of both direct and indirect  selections.  The GEI across the three locations  was very  strong, while the results of pair-wise site analysis  varied between the pairs of locations.  The genetic correlations for pairs of locations  were moderately high between South Sumatra  and Riau;0.68 for dbh and 0.85 for height,  but were lower  between South Kalimantan and the other locations  (0.32 to 0.56). The gains resulting  from direct  selection  were  apparently greater than those resulting  from indirect  selection.  The genetic  gains achieved  in South Sumatra and Riau  would  decrease by 24% as a result  of transfer  to other  sites, while  transfer  from South Kalimantan to Sumatra  Island (and vice versa) would  reduce in the genetic  gain by 60%. Hence, the breeding  population in South Kalimantan should be developed separately from those in South Sumatra  and Riau